Rejection of Samoan Government toward UN Proposal to Change Its Status from Least Developed Country to Developing Country - Festy Adhanita Soebagyo (2009)
ABSTRACT The research discussed about the rejection of Samoan Government toward UN proposal on graduation status. The background is the Samoa condition and situation as one of the Least Developed Country member which has structural problems to growth. Especially the factor related to condition of economic and environment which is vulnerable even though Samoa met two of the three graduation criteria. Thereby, the problem formulation of the research is why the Samoan Government rejected the UN